INNOVATIVE SKILLS OF AN EDUCATOR IN THE EDUCATION OF A PERFECT PERSON - Aminova Manzura Mutalibovna; Xabibullayrva Muxlisa (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In articles questions of innovation readiness of the modern teacher are considered and technologies are defined criterion their knowledge innovative pedagogical. According to the author, utility of new pedagogical technologies raises when the teacher can them. And also the author pays special attention in studyingof social studies in the course of globalisation and offers the points of view.